Gold medal policing: operational readiness and performance excellence - McDonald, Judy M. (Routledge series on practical and evidence-based policing, 2025)
"This straightforward, easy-to-understand textbook inspires tools for improving job performance, productivity, and morale in law enforcement. The groundbreaking first edition of Gold Medal Policing confirmed the importance of mental readiness in frontline policing excellence. Partnerships with policing and related fields positioned Gold Medal Policing principles across recruitment, multi-level training, web-based learning, and field assessment. The second edition consolidates two decades of peer-reviewed research and training, reflecting new trends, lessons, contemporary issues, and proven tools. Drawing on insights from frontline officers recognized for their excellence, including coach officers, it introduces an Operational Readiness Framework rooted in scientific principles. This framework systematically assesses physical, technical, and mental readiness, creating a detailed police-specific profile. A comprehensive literature review informs current police preparedness practices. Mental readiness is upheld to strict, measurable standards, akin to traditional physical and technical readiness. Best practices from exceptional officers are isolated, and operational benchmarks and strategies are established. The ultimate result is to empower officers to excel in the practice of their profession. Gold Medal Policing is indispensable for law enforcement leaders, scholars, students, and aspiring officers"--